Analisis Kebijakan Sistem Penerimaan Peserta Didik Baru Serta Implikasinya Terhadap Kualitas Pendidikan - Saadah, Nailis; Wastri , Linda; Trisoni, Ridwal (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2023)
The annual Admission of New Students (PPDB) organized by the government in collaboration with schools is not without challenges. The competition among schools leads to a struggle to attract the best students. Despite being formal educational institutions trusted by the community, schools have a consistenly responsibility to implement their administrators. The admission of new students is based on the provisions of Regulation of the Minister of Education and Culture Number 51 of 2018, carried out through three pathways: zoning, achievement, and parental job relocation. Zoning admission involves admitting students based on the distance from their residence to the school, with a minimum acceptance requirement of 90% of the school's capacity. Achievement admission is based on excellence in either academic or non-academic fields, with a maximum acceptance of 5% of the school's capacity. Parental job relocation admission is for students outside the zoning and achievement pathways, with a maximum acceptance of 5% of the school's capacity.The implementation of the zoning system for new student admissions, as stipulated in Regulation of the Minister of Education and Culture Number 51 of 2018, has implications for the declining motivation of students, an increase in adolescent delinquency, and a decrease in parental responsibility towards students.